Harmonious Synergy of Spirit and Essence: Constructing the Ning'an Model of a County-Level Labor Education System from the Perspective of Regional Culture - Chunxia Guo (Education Research on Study Tours and Practice, 2026)
Against the dual backdrop of the new era’s "Five Education Integration" initiative and the rural revitalization strategy,labor education has been entrusted with the dual missions of "fostering virtue through education" and "serving local communities." Taking Ning'an City,Heilongjiang Province—a national pilot zone for labor education—as the research subject,this paper systematically elaborates on its "Harmonious Synergy of Spirit and Essence" county-level model of labor education,which is built upon the natural resources of the "Jiangnan of the North," the historical and cultural lineage of the Bohai Kingdom,the heritage of the red revolution,and the spirit of agricultural reclamation. The study proposes that Ning'an has established a top-level design featuring multi-departmental collaboration among "administrative bodies,teaching research institutions,schools,and society," setting the dual-core-driven "dual-wing" development goals centered on "Ling (flexible mechanisms)" and "Yun (cultural heritage)." Within schools,a three-tier curriculum system of "compulsory course guidance,interdisciplinary integration,and school-based characteristics" has been constructed,deeply integrating agricultural civilization,smart agriculture,and intangible cultural heritage. Outside schools,three implementation pathways have been innovated: "research and study base platforms,home-school-community co-education,and empowerment through characteristic industries," which transform local economic industries such as Siberian ginseng,ground-grown agaric,and slate rice into labor education resources. Research findings indicate that this model,through the two-way integration of in-school and out-of-school education and the mechanism of deep empowerment of regional industries,has effectively cultivated students' labor literacy,innovative spirit,and local identity,providing replicable "Ning'an experience" for constructing localized and ecological labor education systems in similar regions. Looking ahead,sustained efforts should be made to deepen the construction of four major labor education ecosystems: rice farming culture,strain cultivation,red heritage documentation,and cold-region specialty fruits,thereby advancing labor education from "curriculum implementation" to "ecological construction".